Intelligent Design versus Evolution - Nathan Aviezer (Rambam Maimonides Medical Journal, 2010)
Intelligent Design (ID) burst onto the scene in 1996, with the publication of Darwin’s Black Box by Michael Behe. Since then, there has been a plethora of articles written about ID, both pro and con. However, most of the articles critical of ID deal with peripheral issues, such as whether ID is just another form of creationism or whether ID qualifies as science or whether ID should be taught in public schools. It is our view that the central issue is whether the basic claim of ID is correct. Our goal is fourfold: (I) to show that most of the proposed refutations of ID are unconvincing and/or incorrect, (II) to describe the single fundamental error of ID, (III) to discuss the historic tradition surrounding the ID controversy, showing that ID is an example of a “god-of-the-gaps” argument, and (IV) to place the ID controversy in the larger context of proposed proofs for the existence of God, with the emphasis on Jewish tradition.